Answer:
x = 2
Step-by-step explanation:
A = lw
44 = 4(3x+5)
44 = 12x + 20
24 = 12x
x = 2
Answer:
20kg of $0.89 candy
10kg of $1.10 candy
Step-by-step explanation:
Candy 1 = 0.89 per kg
Candy 2 = 1.10 per kg
Total kilogram, kg = 30
Let candy 1 = x ; candy 2 = (30 - x) ;
0.89x + 1.10(30 - x) = 0.96(30)
0.89x + 33 - 1.10x = 28.8
0.89x - 1.10x = 28.8 - 33
-0.21x = - 4.2
x = 4.2 / 0.21
x = 20
20kg of $0.89 candy
(30 - x) = (30 - 20) = 10kg
10kg of $1.10 candy
Answer:
They both involve writing a rate.
Step-by-step explanation:
EDGENUITY ANSWER
Answer:
<h2>f( - 1) = - 4</h2>
Step-by-step explanation:
f(x) = 3x - 1
To find f(-1) substitute the value of x that's
- 1 into f(x). That's for every x in f(x) replace it with - 1 and solve
That's
f( - 1) = 3(-1) - 1
= - 3 - 1
We have the final answer as
<h3>f(-1) = - 4</h3>
Hope this helps you